THE CONCURRENT ROLE OF THE CENTRAL AND LOCAL GOVERNMENTS IN ADDRESSING THE POVERTY CYCLE IN INDONESIA - Taufik, Muh Bambang; Taqiyuddin BN , Andi Muh.; Arief, Ahmad (PT. Altin Riset Publishing, 2025)
To overcome the cycle of poverty in Indonesia, competition between the central and regional governments creates its challenges. Although various social assistance and economic empowerment programmes have been launched, data from the Central Statistics Agency (BPS) shows that around 9.54% of Indonesia's population still lives below the poverty line in 2023. The reality on the ground shows that the mismatch between policies and the needs of communities at the local level often hinders the effectiveness of programmes. For example, direct cash transfers (BLT) received by communities are often insufficient to meet basic needs due to high living costs. Additionally, overlapping policies and a lack of coordination between the central and local governments cause confusion among beneficiaries. This results in social and economic vulnerability among communities, exacerbating the complexity of poverty issues that should be addressed. Therefore, a more integrated and responsive strategy tailored to local conditions is needed to achieve more effective results in poverty alleviation.